How Porphyromonas gingivalis Navigate the Map: The Effect of Surface Topography on the Adhesion of Porphyromonas gingivalis on Biomaterials - Ardhani, Retno (MDPI, 2022)
The main purpose of this study is to develop an understanding of how Porphyromonas gingivalis responds to subperiosteal implant surface topography. A literature review was drawn from various electronic databases from 2000 to 2021. The two main keywords used were “Porphyromonas gingivalis” and “Surface Topography”. We excluded all reviews and or meta-analysis articles, articles not published in English, and articles with no surface characterization process or average surface roughness (Ra) value. A total of 26 selected publications were then included in this study. All research included showed the effect of topography on Porphyromonas gingivalis to various degrees. It was found that topography features such as size and shape affected Porphyromonas gingivalis adhesion to subperiosteal implant materials. In general, a smaller Ra value reduces Porphyromonas gingivalis regardless of the type of materials, with a threshold of 0.3 µm for titanium.